2004
DOI: 10.1016/s0272-6386(04)01086-8
|View full text |Cite
|
Sign up to set email alerts
|

Epoetin requirements predict mortality in hemodialysis patients

Abstract: Epoetin dose requirement is an independent predictor of total mortality in hemodialysis patients after adjustment for hematocrit. Poor responders who continue to have low hematocrit values despite the administration of high epoetin doses may not necessarily benefit from more epoetin, but perhaps should be considered for other adjunctive therapies. In contrast to conventional wisdom, this study suggests that epoetin dosing requirements could provide important prognostic information beyond that predicted by hema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
101
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 168 publications
(109 citation statements)
references
References 0 publications
7
101
0
1
Order By: Relevance
“…ESA-sensitive patients derive survival benefits from the full correction of anemia, whereas patients with ESA resistance (which is a predictor of poor survival) may be harmed by the high doses of ESA prescribed in the attempt to increase Hb levels [44, 45]; however, this is still under debate [46]. Although higher Hb targets have been suggested to reduce the need for transfusions and have beneficial effects on the quality of life of patients [911], disadvantages have also been reported [1214].…”
Section: Discussionmentioning
confidence: 99%
“…ESA-sensitive patients derive survival benefits from the full correction of anemia, whereas patients with ESA resistance (which is a predictor of poor survival) may be harmed by the high doses of ESA prescribed in the attempt to increase Hb levels [44, 45]; however, this is still under debate [46]. Although higher Hb targets have been suggested to reduce the need for transfusions and have beneficial effects on the quality of life of patients [911], disadvantages have also been reported [1214].…”
Section: Discussionmentioning
confidence: 99%
“…Randomized trials have shown increased mortality 1 or no beneficial clinical effects 2 among those assigned to normal Hct targets, and observational studies 3,4 have found no survival benefits among hemodialysis patients receiving high ESA doses.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, primary outcomes for both trials were composites (including death, myocardial infarction or stroke in CHOIR, death or cardiovascular event including stroke in TREAT) [7, 10]. Other observational studies in adults have shown that ESA dose requirement is a predictor of mortality in adults on HD, independent of hematocrit level [19]. An advantage of examining the association between ESA dose and mortality in a pediatric dialysis cohort is that the prevalence of advanced cardiovascular disease in these patients is comparatively low, and thus we are able to characterize the association without the significantly increased risk conferred to older adults.…”
Section: Discussionmentioning
confidence: 99%